Tension band wiring versus suture anchor technique in patellar inferior pole fracture: Novel double row suture anchor technique. (December 2022) - Park, Yong-Geun; Choi, Sungwook; Kim, Byung Suk; Lee, Seok Jae; Kim, Do-Yeon; Lim, Chaemoon
Abstract: Introduction: Patellar inferior pole fractures are challenging to obtain sufficient fixation. The purpose of this retrospective, case-controlled study was to compare the clinical and radiological outcomes between tension band wiring (TBW) and our novel double-row suture anchor (SA) technique in patellar inferior pole fractures. Materials and methods: This retrospective study included patients who underwent TBW or SA fixation for patellar inferior pole fractures from 2015 to 2019. A total of 63 patients were divided into two groups according to the surgical procedure: the TBW group (n = 35) and the SA fixation group (n = 28). The visual analog scale score, range of motion of the knee, Lysholm score, Kujala patellofemoral score, and patient satisfaction score were evaluated for clinical and functional outcomes. Radiological outcomes included the time to radiological union, loss of reduction, and the Insall–Salvati (IS) ratio. Results: Significant improvements in clinical outcomes were observed in both groups with no significant differences. Bone union was achieved in all patients, and there was no significant difference in the time to radiological union and the IS ratio between the two groups. All patients in the TBW group underwent additional surgeries for implant removal. However, none of the patients in the SA group underwent implant removal or experienced skin irritation. Conclusion: Our novel double-row SA technique could provide comparable fixation strength and good clinical outcomes, with fewer complications in patellar inferior pole fractures. This novel SA technique is a satisfactory alternative treatment for patellar inferior pole fractures. Highlights: This novel double-row suture anchor technique provided good clinical outcomes and fixation strength comparable with tension band wiring in patellar inferior pole fractures. This technique has the advantage of fewer complications without the need for implant removal and is a satisfactory alternative treatment option for patellar inferior pole fractures.